Membangun Kesadaran Orang Tua terhadap Keberagaman dalam Pendidikan inklusi pada Anak Usia Dini - Rendy Amora Jofipasi; Jon Efendi; Robbi Asri (Journal of Special Education Lectura, 2023)
The study highlights the importance of education and training for parents to understand the concept of inclusion, respond to children's differences, and promote a positive attitude towards diversity. Inclusive early childhood education presents new challenges and opportunities in embracing diversity. The main focus of this research is to discuss efforts to build parents' awareness of diversity in the context of inclusive education. The study used a qualitative approach with in-depth interviews and participatory observations of early childhood parents involved in inclusion programs. Research results show that parents' awareness of diversity in inclusive education is influenced by factors such as knowledge, personal experience, and community perception. In addition, collaboration between educational institutions and parents is considered crucial in creating an educational environment that supports children with special needs. Faced with these diverse challenges, the study provides recommendations for developing socialization programmes for parents, strengthening inter-stakeholder communication, and improving access to information related to inclusion. By building parental awareness, it can be the key to achieving inclusive and sustainable education in early childhood.